Sex and gender influence on immunity and autoimmunity - Lahita, Robert G. (Frontiers in Immunology, 2023)
Autoimmune Diseases are skewed toward one biological sex or another. This is the obvious observation of many decades, and it remains unexplained. Females predominate with most autoimmune diseases. The reasons for this predilection are an interplay of genetic, epigenetic and hormonal factors.